Description of three new species of Wormaldia McLachlan, 1865 from Vietnam (Trichoptera: Philopotamidae) - Kjell Arne Johanson; Hong-Thai Pham (European Journal of Taxonomy)
Three previously unknown species of Wormaldia McLachlan, 1865 are herein described from the Cao Bang Province, N Nui Pia Oac Nature Reserve, located in northern Vietnam: Wormaldia piadenensis sp. nov., Wormaldia nui sp. nov., and Wormaldia caobangensis sp. nov. These species are considered rare and encountered either as singletons or as a pair. The specimens were collected in 2012 using Malaise traps and light traps, which were strategically positioned along stream banks. Additionally, a key for the identification of the male individuals of the 19 known species of Wormaldia in Vietnam is provided.